IRRITATION TEST AND PHYSICAL PROPERTIES OF UNGUENTUM VOLATILE OIL OF Syzygium aromaticum IN HYDROCARBON BASE - Neneng Rachmalia Izzatul Mukhlishah; Nining Sugihartini; Tedjo Yuwono (Majalah Farmaseutik, 2016)
Essential oil of clove (Syzygium aromaticum) with the active compound eugenol has been widely studied and well known efficacious as antiinflammatory, and advanced research related to the formulation continues. Formula in this study was the topical dosage form an ointment using a hydrocarbon base (Vaseline album and Paraffin liquidum). Aim of this study was to know the physical properties and the power of irritation from ointment of clove essential oil (MABC) hydrocarbon base. The ointment was made by the melting method with concentration of MABC 5% (F1), 10% (FII) and 15% (FIII). Then the ointment of the third formula was evaluated its physical properties (spreadibility, adhesivity and pH). It was also evaluated the irritation’s properties on the skin by using a male guinea pigs test animals by the method of Draize test. The data were analyzed statistically with a confidence level of 95%. The statistical shows that were method significant differences between the formula. The increasing concentration of MABC, causes the greater of spreadibility (p<0,05) and adhesivity (p <0.05 between F 1 and FIII). On the other hand, the Kruskal Wallis test of pH shows there was no significant difference (p> 0.05). The results of irritation Draize test shows that an ointment base MABC hydrocarbon with concentration of 5%, 10% and 15% does not cause irritation.